DRAMATURGY, SPLIT PERSONALITY AND THE QUESTION OF IDENTITY IN EFFIONG JOHNSON’S SON OF THE LAND - Udofia, Anietie Francis (International Review of Humanities Studies, 2021)
The nature of man in relationship with his society is ambivalent, reflecting that human beings have the capacity to alter their personality to fit in to the situation they are confronted with at different times. This alterations result in indeterminate portrayal of human identity in creative works. No character is whole until the social condition he is pitched against justifies him. This paper evaluates Effiong Johnson’s treatment of indeterminacy of the human selves in a chaotic social milieu in Son of the Land. It uses qualitative research methodology and bases its theoretical framework on Sigmund Freud’s Psychodynamic Theory. Findings show that uncertainty of social conditions may force people to vary the attitudes they put up for survival. Dramaturgy is the various impressions people put up at different times. Personality is the discernible self marked for a particular regular situation, while the quirk in the marked self suggests split-personality. The totality of all selves in their sameness or differentiation in the confrontations with pleasant and unpleasant situations in life suggests human identity. The paper concludes that unstable society will provide unstable citizens. The circumstances people face in life shape their pattern of thought which motivates action they take. Everyone puts up a self when confronted with a happenstance. The knowledge of human behaviour should be broadened in drama to help in the curtailment of sweeping conclusion over human attitude, varying selves and identity in the society.